2017
DOI: 10.1159/000477135
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Differentiation Modulated by Polymeric Membrane Properties

Abstract: In this study, different collagen-blend membranes were successfully constructed by blending collagen with chitosan (CHT) or poly(lactic-co-glycolic acid) (PLGA) to enhance their properties and thus create new biofunctional materials with great potential use for neuronal tissue engineering and regeneration. Collagen blending strongly affected membrane properties in the following ways: (i) it improved the surface hydrophilicity of both pure CHT and PLGA membranes, (ii) it reduced the stiffness of CHT membranes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To further investigate the effect of environmental elasticity on neurite development, we examined neurite lengths in 3D collagen. Numerous studies have used collagen I matrices to study the effects of variable elastic conditions on cell shape, polarity, and durotaxis (Sundararaghavan et al., 2009, Willits and Skornia, 2004), as well as differentiation, neuritogenesis, and nerve regeneration (Gil and del Rio, 2012, Morelli et al., 2017, Musah et al., 2014). To test whether altering collagen elasticity affected hMN and hFB neurite outgrowth in three dimensions, we cultured neurospheres on top of 1.5 mg/mL fibrillar collagen I.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the effect of environmental elasticity on neurite development, we examined neurite lengths in 3D collagen. Numerous studies have used collagen I matrices to study the effects of variable elastic conditions on cell shape, polarity, and durotaxis (Sundararaghavan et al., 2009, Willits and Skornia, 2004), as well as differentiation, neuritogenesis, and nerve regeneration (Gil and del Rio, 2012, Morelli et al., 2017, Musah et al., 2014). To test whether altering collagen elasticity affected hMN and hFB neurite outgrowth in three dimensions, we cultured neurospheres on top of 1.5 mg/mL fibrillar collagen I.…”
Section: Resultsmentioning
confidence: 99%
“…Besides stiffness, ultimate tensile strength (UTS) and elongation at break [ε] also influence the overall biomechanical characteristics of the PLGA membrane, which have been defined and reported in Table 1. In a previous work, aimed at disclosing the effect of membrane mechanical properties for the reconstruction of a neuronal tissue analogue [15], we showed that UTS and elongation at break are two key parameters able to influence growth cone formation and axonal and dendritic complex arborization. The mechanical features of brain tissue are quite peculiar, being anisotropic and extremely soft (e.g., <1 kPa) [22].…”
Section: Characterization Of Plga Membrane Propertiesmentioning
confidence: 97%
“…Membranes of Poly(D,L-lactide-co-glycolide) (PLGA) were prepared in a flat configuration using a phase inversion technique with solvent evaporation, as described elsewhere [15]. In brief, PLGA (10% w/v) (MW 50,000-75,000 Da, Sigma-Aldrich, St. Louis, MO, USA) was dissolved in 1.4-dioxan.…”
Section: Preparation Of Plga Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, decades of advances in membrane technology have led to its application in neuroscience and neural engineering. Several papers indicated that membrane-based systems provide in vitro advanced devices that enhance neuronal growth and differentiation and enable the repair and regeneration of the nervous system [De Bartolo et al, 2008;Morelli et al, 2010Morelli et al, , 2015bMorelli et al, , 2017a. In addition, neuronal biohybrid membrane systems can mimic specific features of the in vivo neuronal environment and, therefore, are also widely used as in vitro brain tissue models for pharmacological screening and as investigational platform for neurodegenerative diseases [Giusi et al, 2009;Morelli et al, 2014Morelli et al, , 2016Morelli et al, , 2019Morelli et al, , 2021Piscioneri et al, 2015Piscioneri et al, , 2021Mele et al, 2017].…”
Section: Fiber-based Approaches For Neuronal Tissue Applicationsmentioning
confidence: 99%